Unemployment in Indonesia: An Analysis of Economic Determinants from 2012-2021 - Agustina, Mei; Astuti, Hartiningsih; Susilo, Joko Hadi (Signifikan: Jurnal Ilmu Ekonomi, 2023)
The economic problem is one of the things that the Indonesian government must consider. One of them is unemployment because it impacts the socioeconomic conditions of society. This condition is necessary to suppress or reduce the unemployment rate. This research was conducted to determine the conditions and variables affecting Indonesia's unemployment rate. The data analysis used is an econometric model on dynamic panel data using the Generalized Method of Moments (GMM) developed by Arellano Bond. The study results show that the Human Development Index, inflation, minimum wages, and worker numbers significantly influence Indonesia's unemployment. In addition, the unemployment lag also has a significantly positive effect on unemployment. The findings of this study provide information on strategies for increasing the demand and supply of labor, wage regulation, search, match effectiveness in the labor market, and realistic short- and long-term policies. JEL Classification: C33, E24, J64 How to Cite:Agustina, M., Astuti, H., & Susilo, J. H. (2023). Unemployment in Indonesia: An Analysis of Economic Determinants from 2012-2021. Signifikan: Jurnal Ilmu Ekonomi, 12(1), 69-82. https://doi.org/10.15408/sjie.v12i1.29247.